Value and Vulnerability : An Interfaith Dialogue on Human Dignity - Rothchild, Jonathan; Petrusek, Matthew R. (Book collections on Project MUSE., 2020)
Value and Vulnerability brings together scholars of many religions--including Catholicism, Buddhism, Judaism, Hinduism, Eastern Orthodoxy, Protestantism, Islam, and Humanism--to identify and examine conceptions and interpretations of dignity within different religious and philosophical perspectives and their applications to contemporary issues of conflict, such as gendered, religious, and racial violence, immigration, ecology, and religious peacemaking. Value and Vulnerability also includes response chapters that clarify and refine these interpretations from interfaith perspectives. Through this volume, Matthew R. Petrusek and Jonathan Rothchild offer recommendations for advancing the conversation about dignity within and among traditions and for addressing urgent global issues and threats to dignity. Together, Petrusek, Rothchild, and the contributors create a comparative framework constituted by seven questions: What sources justify dignity's existence, nature, and purpose? What is the relationship between the divine and human dignity? What is the relationship between dignity and the human body? Is dignity vulnerable or invulnerable to moral harm? Is dignity inherent or attained? Is dignity universal and equal? Is dignity practical? Through its systematic, comparative, interdisciplinary, and practical dimensions, Value and Vulnerability fills in the gaps in contemporary theological, philosophical, and ethical discourses on dignity. --